HEPATITIS A SEROLOGY IN MOTHERS AND THEIR BABIES IN THE FIRST SIX MONTHS OF LIFE - (:unkn) unknown (ISTANBUL UNIV, FAC MEDICINE, PUBL OFF, 2019)
Objective: Epidemiology of hepatitis A infection differs according to living conditions. Therefore, evaluating the changing epidemiology of the disease is important for preventive medicine. The aim of the study was to determine the seropositivity of hepatitis A antibody in mothers and their babies and to evaluate the factors affecting it. Materials and Methods: The data of 209 mother-infant pairs were evaluated. Blood samples were collected from mothers one month after birth and at 1 and 6 months of age from their babies. Hepatitis A IgG antibody levels were determined by ELISA method. The socio-economic and demographic characteristics of the families were collected by a questionnaire. Results: The seropositivity of the hepatitis A antibody was 67% in mothers at one month after birth, 66.1% and 68.9% in their babies at 1 and 6 months of age respectively. Parental education, family monthly income, gravity and parity were found to have a statistically significant effect on hepatitis A seropositivity. As the level of education and monthly income increased, hepatitis A seropositivity decreased. On the other hand as parity and gravida increased, seropositivity increased as well. Conclusion: Hepatitis A seropositivity in infants is thought to be affected by socio-economic factors.
Keywords: Hepatitis A; maternal antibodies; infants; SEROPREVALENCE; ANTIBODIES; EPIDEMIOLOGY; INFECTION; CHILDREN; TURKEY